A thematic-cognitive perspective for exploring the writing skills of children: a textual analysis using ENA - Jianheng Zhang; Tiong-Thye Goh; Dexin Chen; Yuan Gong; Bing Yang; Liqin Pan; Ting Song; Shiqi Yu; Hanzhen Li (Frontiers in Psychology)
IntroductionPrimary school is a critical period for children’s language development, coinciding with rapid cognitive growth that supports the emergence of writing skills. Understanding how children’s cognitive structures manifest in writing is essential for improving instructional strategies.MethodsThis study employed epistemic network analysis (ENA) to encode and analyze six years of student writing data. Cognitive network maps were constructed to examine developmental trends and differences across grades and genders from both subject-matter and cognitive perspectives.ResultsThe analysis demonstrates ENA’s effectiveness in visualizing the cognitive features embedded in written texts. Distinct patterns emerged across subjects, grades, and genders, revealing a complex and nuanced cognitive network structure.DiscussionThese findings highlight important nuances in children’s writing development. Recognizing subject-specific, developmental, and gender-related cognitive differences can inform more personalized and effective writing instruction.